Preparation method of nanoscale elemental Ni and application of nanoscale elemental Ni in catalytic hydrogen storage

Through wet chemistry method and the use of 1,2-propylene glycol, nano-sized metal element Ni was successfully prepared below 10 nm, solving the problem of large size and weak catalytic activity of the single metal catalyst, achieving efficient and stable catalytic effect, reducing the Preparation cost.

CN119407161AInactive Publication Date: 2025-02-11GUILIN UNIV OF ELECTRONIC TECH

Patent Information

Application Number
CN202411554310.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the single metal catalyst has a large size, weak catalytic activity, easy to agglomerate, and the method of preparing nano-scale metal element is complex and costly, which cannot meet the needs of large-scale production.

Method used

The simple wet chemistry method is used to reduce the agglomeration of Ni metal element by adding a viscous organic solvent 1,2-propanediol, and reduce the reaction temperature and time to prepare nano-scale metal element Ni with a size of less than 10 nm.

Benefits of technology

It realizes uniform dispersion and structural stability of nano-scale metal element Ni, reduces preparation cost and technical complexity, improves the catalytic efficiency and stability of the catalyst, and is suitable for hydrogen storage materials and fuel cells and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119407161A_ABST
    Figure CN119407161A_ABST
Patent Text Reader

Abstract

The invention discloses nanoscale simple substance Ni which is prepared by taking nickel chloride hexahydrate, sodium hydroxide and 1, 2-propylene glycol as raw materials and performing water bath heating reduction through a reducing agent hydrazine hydrate. The size of the obtained nanoscale simple substance Ni is 5-10 nm, and particles are uniformly dispersed and are stable in structure. MgH2 and the prepared nanoscale simple substance Ni are subjected to ball milling, and the magnesium hydride composite hydrogen storage material based on the nanoscale simple substance Ni as the catalyst, namely Ni / MgH2 for short, can be obtained. The initial dehydrogenation temperature of the obtained Ni / MgH2 hydrogen storage system is 195 DEG C; under the conditions that the dehydrogenation temperature is 325 DEG C and the dehydrogenation time is 500 seconds, the dehydrogenation amount is 6.5 wt%; under the conditions that the hydrogen absorption temperature is 150 DEG C and the hydrogen absorption time is 1000 seconds, the hydrogen absorption amount is 4.0 wt%. The prepared catalyst is used for catalyzing MgH2 reaction and has the characteristics of high activity, high selectivity and high stability. The preparation method disclosed by the invention is low in cost, simple in steps, relatively good in repeatability and easy for mass production, and the obtained elemental Ni has a good catalytic effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage materials, and in particular to a method for preparing nano-scale elemental Ni and its application in catalytic hydrogen storage. Background Art

[0002] At present, single metal catalysts, especially transition metal catalysts, have excellent effects in improving the hydrogen storage performance of MgH2. Ni has attracted considerable attention due to its active role in the hydrogen dissociation process, in which the empty d orbital of Ni first accepts the electrons of hydrogen and then stabilizes the combination by reversely providing electrons from the filled d orbital to the antibonding orbital (σ*) of H2, thereby promoting the breaking of the HH bond. In particular, nanoscale Ni-based catalysts are very effective, such as document 1 (XL Zhang, YF Liu, X. Zhang, JJ Hu, MX Gao, HGPan, Em-powering hydrogen storage performance of MgH2 by nanoengineering and nanocatalysis, Mater. Today Nano. 9 (2020) 10064) It is proved that Ni can provide a larger contact surface area and abundant active sites, which helps to reduce the amount of its effective catalyst added, thereby minimizing the loss of theoretical hydrogen storage capacity. However, due to the high surface energy, nanoscale Ni particles are unstable in size and easily agglomerate during the hydrogen adsorption cycle.

[0003] Therefore, recently, some scholars have studied the effect of the size of Ni nanoparticles on the hydrogen storage performance of MgH2. For example, in the literature 2 (Wang S, Gao M, Yao Z, et.al. High-loading, ultrafine Ni nanoparticles dispersedon porous hollow carbon nanospheres for fast (de) hydrogenation kinetics of MgH2, [J]. Journal of Magnesium and Alloys, 2022, Volume 10 (Issue 12): Pages 3354-3366.), a composite catalyst with high loading of ultrafine Ni nanoparticles uniformly dispersed on porous hollow carbon nanospheres was developed, which showed excellent catalytic activity for the hydrogen storage performance of MgH2, so the addition of Ni has a positive effect on the MgH2 system.

[0004] However, most single metal catalyst preparation methods are prone to agglomeration, and the impact of large catalyst particle size on the hydrogen storage performance of MgH2 cannot meet its application requirements. Secondly, most nano-scale catalyst preparation technologies are relatively complex and cannot be mass-produced, resulting in high costs. Summary of the invention

[0005] The purpose of the present invention is to provide a nano-scale metal element Ni and a preparation method thereof and an application thereof as a hydrogen storage catalyst.

[0006] Based on the research and analysis of the above technical background, the following conclusions can be drawn:

[0007] 1. Currently, the size of the doped single metal catalyst is large and its catalytic activity for MgH2 is weak;

[0008] 2. Currently, doping with a single metal catalyst will cause agglomeration;

[0009] 3. The current method for preparing nano-scale metal elements is complex, costly and has a low yield.

[0010] In view of the technical problems existing in the prior art, the present invention adopts a simple wet chemical method to prepare nano-scale metal element Ni as a hydrogen storage catalyst to achieve the following invention objectives:

[0011] 1. By adding the viscous organic solvent 1,2-propylene glycol, the agglomeration of Ni metal elements during the reaction process is reduced, and the catalyst is evenly dispersed;

[0012] 2. Reduce the size of the catalyst by reducing the reaction time and temperature while reducing the preparation process technology and cost.

[0013] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0014] A nano-scale metal single substance Ni is prepared by reducing nickel chloride hexahydrate, sodium hydroxide and 1,2-propylene glycol as raw materials by heating in a water bath with a reducing agent, hydrazine hydrate;

[0015] The obtained nano-scale metal single substance Ni has uniform size and stable structure, and the size is less than 10nm. A method for preparing nano-scale metal single substance Ni:

[0016] Mix nickel chloride hexahydrate with 1,2-propylene glycol, mix sodium hydroxide with 1,2-propylene glycol and stir vigorously to obtain solutions A and B; then, under certain conditions, mix solution A with solution B and stir vigorously, add reducing agent hydrazine hydrate, stir and heat to complete the reaction, centrifuge and wash the reaction product with deionized water and anhydrous ethanol respectively under certain conditions, and finally, vacuum dry under certain conditions to obtain nano-scale metal single substance Ni;

[0017] In the method, the mass ratio of nickel chloride hexahydrate to sodium hydroxide is 5:2; the volume ratio of 1,2-propylene glycol as a solvent in solutions A and B is 3:2;

[0018] In the method, the conditions for water bath heating are: the reaction temperature is 80-100°C and the reaction time is 1-2h;

[0019] In the method, the centrifugal washing conditions are: the centrifugal washing speed is 5000-7000 rpm, and the centrifugal washing time is 3-5 minutes; the drying conditions are: the drying temperature is 60-80° C., and the drying time is 10-12 hours.

[0020] A preparation method of a magnesium hydride composite hydrogen storage material based on nano-scale metal single substance Ni, wherein MgH2 and metal single substance Ni meet a certain mass ratio and are ball-milled under certain conditions to obtain a magnesium hydride composite hydrogen storage material based on metal single substance Ni, referred to as Ni / MgH2;

[0021] The mass ratio of MgH2 to metal element Ni is 47:3;

[0022] The ball milling conditions are as follows: the ball milling speed is 450 rpm, the ball milling time is 4 h, and the ball-to-material ratio is 60:1;

[0023] The initial dehydrogenation temperature of the obtained Ni / MgH2 is 195°C; under the conditions of a dehydrogenation temperature of 325°C and a dehydrogenation time of 300s, the dehydrogenation amount is about 6.4wt%; under the conditions of a hydrogen absorption temperature of 150°C and a hydrogen absorption time of 1000s, the hydrogen absorption amount is 3.9-4.0wt%.

[0024] The technical effects of the present invention have been tested and the specific contents are as follows:

[0025] The invention has been tested by XRD and found that the diffraction peak of Ni is consistent with the characteristic peak of standard Ni. The result proves the successful preparation of Ni.

[0026] According to the present invention, TEM detection shows that the size of the metal single substance Ni is less than 10 nm.

[0027] The dehydrogenation test of the present invention shows that when the doping amount of the metal element Ni is 4-8wt%, the initial dehydrogenation temperature is 188-195°C and the dehydrogenation amount is 6.8-7.1wt%.

[0028] In summary: the successfully prepared nano-scale metal element Ni can have good catalytic activity for magnesium hydride.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] 1. Nano-scale metal element Ni itself has the characteristics of stable properties and structure and is not easy to be destroyed; its particle size is small, providing more catalytic active sites, thereby increasing the catalytic efficiency of the catalyst;

[0031] 2. The raw materials used are commercially available, the process is simple, and low energy consumption and pollution are achieved.

[0032] Therefore, compared with the prior art, the present invention has better MgH2 hydrogen storage catalytic performance, improves the stability and catalytic activity of the catalyst, and has broad application prospects in the fields of hydrogen storage materials, fuel cells, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the XRD pattern of the nano-metal single substance Ni prepared in Example 1;

[0034] Figure 2 The XRD pattern of the metal element Ni prepared in Comparative Example 1;

[0035] Figure 3 TEM image of the prepared nano-metal single substance Ni in Example 1;

[0036] Figure 4 The HAADF diagram and EDS spectrum diagram of the prepared nano-metal single substance Ni in Example 1;

[0037] Figure 5 The prepared nano-metal single substance Ni in Comparative Example 1 (H2O) TEM images of

[0038] Figure 6 The TPD diagrams of 6-Ni / MgH2, 4-Ni / MgH2 and 8-Ni / MgH2 prepared in Example 1, Comparative Example 2 and Comparative Example 3;

[0039] Figure 7 This is the hydrogen release diagram of 6-Ni / MgH2 prepared in Example 1 at 325°C;

[0040] Figure 8 This is the hydrogen absorption diagram of 6-Ni / MgH2 prepared in Example 1 at 150°C. DETAILED DESCRIPTION

[0041] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0042] Example 1

[0043] A method for preparing nano-scale metal element Ni:

[0044] 2.5g of nickel chloride hexahydrate and 30ml of 1,2-propylene glycol are mixed, and 1g of sodium hydroxide and 20ml of 1,2-propylene glycol are mixed and stirred vigorously to obtain solutions A and B; then, under certain conditions, solution A and solution B are mixed and stirred vigorously, 5ml of hydrazine hydrate is added, stirred and heated, and after the reaction is completed, the centrifugal washing liquid is deionized water and anhydrous ethanol respectively, under certain conditions, the reaction product is centrifuged and washed, and finally, vacuum drying is performed under certain conditions to obtain nano-scale metal single substance Ni;

[0045] In order to prove the composition of nano-scale metal element Ni, XRD test was carried out. The test results are as follows Figure 1 As shown, the diffraction peak of Ni is consistent with the characteristic peak of standard Ni. The test results show that the preparation is successful.

[0046] In order to prove the microstructure of nano-scale metal element Ni, TEM test was carried out. The test results are as follows Figure 3 As shown, a nanocatalyst with small particle size and uniform distribution was prepared.

[0047] In order to demonstrate the effect of metallic Ni as a MaH2 catalyst, a magnesium hydride composite hydrogen storage material based on metallic Ni was prepared.

[0048] A method for preparing a magnesium hydride composite hydrogen storage material based on nano-scale metal single substance Ni, wherein the mass ratio of MgH2 to nano-scale metal single substance Ni is 47:3, ball milling is performed at a ball milling speed of 450 rpm, a ball milling time of 4 hours, and a ball-to-material ratio of 60:1, to obtain a magnesium hydride composite hydrogen storage material based on nano-scale metal single substance Ni, referred to as Ni / MgH2. The Ni / MgH2 obtained in specific embodiment 1 is named 6-Ni / MgH2.

[0049] In order to prove the hydrogen desorption performance of 6-Ni / MgH2, TPD test and PCT test were carried out; for comparison, TPD test and PCT test were also carried out on pure ball-milled MgH2.

[0050] The TPD test results of pure ball-milled MgH2 are as follows Figure 5 As shown, the initial hydrogen release temperature is 250°C;

[0051] The TPD test results of 6-Ni / MgH2 are as follows Figure 5 As shown, the initial hydrogen release temperature is 195°C;

[0052] Therefore, the TPD test results show that the addition of nano-metal element Ni significantly reduces the initial hydrogen desorption temperature of MgH2 by 55°C.

[0053] The PCT test results of 6-Ni / MgH2 are as follows Figure 6 As shown, when the hydrogen desorption temperature is 325°C, it only takes 500s to reach the maximum hydrogen desorption amount; when the hydrogen absorption temperature is 150°C and the hydrogen absorption time is 1000s, the hydrogen absorption amount is 3.9-4.0wt%.

[0054] The PCT test results show that the addition of nano-scale metal element Ni greatly improves the hydrogen desorption kinetics.

[0055] In order to demonstrate the role of the organic solvent 1,2-propylene glycol in the preparation of nano-metallic single substance Ni, a comparative example 1 is provided to prepare a magnesium hydride composite hydrogen storage material based on metal single substance Ni using deionized water as a solvent.

[0056] Comparative Example 1

[0057] A method for preparing a magnesium hydride composite hydrogen storage material of a metal element Ni based on deionized water as a solvent, wherein the steps not specifically described are the same as those in Example 1, except that deionized water is used instead of 1,2-propylene glycol as the solvent required for preparing the catalyst metal element Ni.

[0058] The XRD pattern of the obtained metal element Ni is as follows: Figure 2 As shown, the diffraction peak of Ni is consistent with the characteristic peak of standard Ni, but there are some oxidation peaks, and the sample is not pure.

[0059] The TEM of the obtained metal element Ni is as follows Figure 4 As shown, the prepared catalyst has a particle size larger than that of nano-metal Ni, but does not reach the particle size of a nano-scale catalyst.

[0060] Comparative Example 2

[0061] A method for preparing a magnesium hydride composite hydrogen storage material with a nano-metal single substance Ni addition amount of 4wt%. The steps not specifically described are the same as those in Example 1, except that when preparing the composite hydrogen storage material, the mass ratio of MgH2 to the nano-metal single substance Ni is 24:1, and the obtained material is named 4-Ni / MgH2.

[0062] The TPD performance test results of 4-Ni / MgH2 are as follows Figure 3 As shown, the initial hydrogen desorption temperature is 200°C and the hydrogen desorption amount is 7.2wt%.

[0063] By comparing with Reference Example 1, it can be seen that the addition of 4-Ni / MgH2 can reduce the initial dehydrogenation temperature of MgH2 by 50°C. The reason is that although the introduction of metal element Ni into MgH2 will form many defects on the Ni / MgH2 interface, such defects greatly contribute to the splitting of H2 molecules and the recombination of hydrogen atoms, ultimately improving the catalytic effect and lowering the initial dehydrogenation temperature, the concentration of the hydrogen pump decreases due to the reduction in the amount of additives added, resulting in fewer reaction sites, so the catalytic performance is not significantly improved.

[0064] Comparative Example 3

[0065] A method for preparing a magnesium hydride composite hydrogen storage material with an addition amount of 8wt% of nano-metal element Ni. The steps not specifically described are the same as those in Example 1, except that when preparing the composite hydrogen storage material, the mass ratio of MgH2 and nano-metal element Ni is 23:3, and the obtained material is named 8-Ni / MgH2.

[0066] The TPD performance test results of 8-Ni / MgH2 are as follows Figure 3 As shown, the initial hydrogen desorption temperature is 188°C and the hydrogen desorption amount is 6.8wt%.

[0067] By comparing with Comparative Example 2, it can be seen that with the addition of 8-Ni / MgH2, as the amount of addition increases, the number of reaction sites increases, so the initial hydrogen desorption temperature is lower than 200°C of 4-Ni / MgH2, but as the number of by-products increases, the amount of hydrogen desorption decreases. The results show that the catalytic performance of 8-Ni / MgH2 is higher than that of 4-Ni / MgH2.

[0068] The following conclusions can be drawn from the above examples:

[0069] By adding nano-metal single substance Ni, a Ni / MgH2 system is constructed, the contact sites between the catalyst and MgH2 are increased, and the catalytic effect is improved, so that the initial dehydrogenation temperature is lower. However, with the increase of additives, the channels for electron transmission increase, the reaction sites also increase, the catalytic effect is also improved, and the reaction by-products increase, reducing the maximum dehydrogenation amount. The results show that at different addition amounts, compared with 4-Ni / MgH2, the initial dehydrogenation temperature of MgH2 is reduced to 200°C, and 8-Ni / MgH2 reduces the initial dehydrogenation temperature of MgH2 to 188°C. In Example 1, 6-Ni / MgH2 can reduce the initial temperature to 195°C. However, considering the initial dehydrogenation temperature and the maximum dehydrogenation amount, the composite material of 6-Ni / MgH2 is selected.

Claims

1. A nano-scale elemental Ni, characterized in that: The obtained nano-scale single-substance Ni has a size of 5-10 nm, and the particles are evenly dispersed and have a stable structure.

2. A method for preparing nano-scale elemental Ni, characterized in that: Nickel chloride hexahydrate is mixed with 1,2-propylene glycol, sodium hydroxide and 1,2-propylene glycol are mixed and stirred vigorously to obtain solutions A and B; then, under certain conditions, solution A is mixed with solution B and stirred vigorously, reducing agent hydrazine hydrate is added, stirred and heated, and after the reaction is completed, the reaction product is centrifuged and washed with deionized water and anhydrous ethanol respectively under certain conditions, and finally, vacuum dried under certain conditions to obtain nano-scale metal single substance Ni.

3. The method for preparing the nano-scale metal element Ni according to claim 2, characterized in that: The mass ratio of nickel chloride hexahydrate to sodium hydroxide is 5:2; the volume ratio of 1,2-propylene glycol as a solvent in solutions A and B is 3:

2.

4. The method for preparing the nano-scale metal element Ni according to claim 2, characterized in that: The conditions for water bath heating are: reaction temperature is 80-100°C and reaction time is 1-2h.

5. The method for preparing the nano-scale metallic element Ni according to claim 2, characterized in that: The conditions for centrifugal washing are: a centrifugal washing speed of 5000-7000 rpm, and a centrifugal washing time of 3-5 minutes; the conditions for drying are: a drying temperature of 60-80° C., and a drying time of 10-12 hours.

6. A method for preparing a magnesium hydride composite hydrogen storage material based on metal element Ni, characterized in that: By ball milling MgH2 and metallic element Ni in a certain mass ratio under certain conditions, a magnesium hydride composite hydrogen storage material based on metallic element Ni can be obtained, which is referred to as Ni / MgH2.

7. The method for preparing the composite hydrogen storage material according to claim 6, characterized in that: The mass ratio of MgH2 to metal element Ni is 47:

3.

8. The method for preparing the composite hydrogen storage material according to claim 6, characterized in that: The ball milling conditions are as follows: the ball milling speed is 450 rpm, the ball milling time is 4 h, and the ball-to-material ratio is 60:

1.

9. The method for preparing the composite hydrogen storage material according to claim 6, characterized in that: The initial dehydrogenation temperature of the obtained Ni / MgH2 was 195°C.

10. The method for preparing the composite hydrogen storage material according to claim 6, characterized in that: The dehydrogenation amount of the obtained Ni / MgH2 is 6.5wt% under the conditions of a dehydrogenation temperature of 325°C and a dehydrogenation time of 500s; the hydrogen absorption amount of the obtained Ni / MgH2 is 4.0wt% under the conditions of a hydrogen absorption temperature of 150°C and a hydrogen absorption time of 1000s.

Citation Information

Patent Citations

  • Monoatomic catalyzed magnesium hydride solid hydrogen storage material, application and preparation method

    CN115784147A

Cited By

  • Nickel-based catalyst for magnesium hydride modification, in-situ preparation method and hydrogen storage material

    CN122424821A